A Case of Celiac Disease Presenting with Recurrent Attacks of Quadriparesis (Journal of Dhaka Medical College, 2017)
Celiac disease, once considered a rare disease in Bangladeshi population, have recently been reported more frequently. Recognition of celiac disease is not easy and a high degree of suspicion in required. Although the disease presents usually with malabsorption syndromes, atypical presentations also may occur which may cause confusion in making a prompt diagnosis. We intend to report a case who presented primarily with flaccid type of quadriparesis who ultimately was proven to be a case of celiac disease. Although neurological symptoms have been associated with celiac disease, motor weakness is very uncommon. We have proposed that in our case electrolyte imbalance have caused or contributed in causing this motor weakness.J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 138-141